Efficacy of blue heat-treated rotary file in primary molar pulpectomy: a case report - Huayta-Guerra, Gerardo Jose (2025)
One of the main advantages of using a continuous rotary system in pulpectomies is the reduction in instrumentation time. This case presents a 3-year and 11-month-old girl who, upon intraoral clinical examination, exhibited a deep and extensive carious lesion with pulpal involvement in tooth 85. Radiographically, an occlusal radiolucent image was observed, clearly indicating pulpal involvement, consistent with pulpal necrosis and chronic apical periodontitis. A pulpectomy was performed using the NiTi Race® Evo #25/06 rotary system at 500 rpm and with a torque of 2.1 Ncm. In the clinical examination, the surrounding gingival tissues were in good condition. Radiographically, there was no evidence of root resorption or signs of infection, and bone regeneration was observed at the furcation level. The rotary system proved to be effective in both shaping and filling the canals, reducing the time required for instrumentation.